ITS-PCR-RFLP analysis of Ganoderma sp. infecting industrial crops - Syd Ali, Nusaibah; Zakaria, Latiffah; A. R., Hassaan (Universiti Putra Malaysia Press, 2011)
Ganoderma is a disastrous pathogen that has been causing tremendous losses to economically important crops in many countries. Vast genetic variations have been observed among several Ganoderma species, even from the same host. In this study, genetic variation was assessed among 44 isolates of Ganoderma sp. isolated from the basidiocarps of four different hosts (oil palm, rubber, tea, and forest trees) collected from selected areas of Peninsular Malaysia. Restriction Fragment Length Polymorphism (RFLP) technique, using ITS1 and ITS4 primers, was used to amplify Internal Transcribed Spacer (ITS) regions. Amplified products were further digested using Bsu 151, Hind III and Taq I restriction enzymes. Cluster analysis with UPGMA using genetic distances clustered all the isolates studied into four main groups. Generally, Ganoderma isolates from the same host were clustered together. The isolates from tea and rubber were more closely related compared to oil palm and forest trees. Similarly, the Ganoderma isolates from the same host were also clustered together, and three species were identified, namely, G. boninense (from oil palm and coconut stumps), G. philippii (rubber) and G. australe (forest trees). The results obtained from the analysis showed that host preference was a possible factor in the differentiation of Ganoderma species.